Insights on COVID-19 Vaccination in Portugal: A Qualitative Study among Health Professionals and Teachers - Estrela, Marta (2022)
Background: Vaccination against COVID-19 has had a major impact over the course of the pandemic, leading to a reduced number of hospitalizations and deaths. However, the mass vaccination process has been accompanied by skepticism and hesitancy since its beginning. As health professionals and teachers are important public health actors who can strongly intervene to reduce vaccination hesitancy among their patients and students, respectively, this study aimed to assess their main perceptions towards COVID-19 vaccination. Methods: Two focus group sessions, one with health professionals and the other with teachers, were conducted according to the COREQ checklist. Qualitative data were analyzed through theoretical thematic analysis. Results: In general, none of the groups showed vaccine hesitancy, although both groups had concerns regarding the safety and efficacy of the vaccines. The main concerns of health professionals were mostly related to the long-term impact of the COVID-19 pandemic, while teachers were more worried about the lack of access to reliable information about the COVID-19 vaccination. Conclusions: It is plausible to conclude that it is imperative to provide clear and accurate information for the population in order to avoid vaccination hesitancy.